A simple method for obtaining wave directional spreading. Issue 2 (3rd July 2017) - Malliouri, Dimitra I.; Memos, Constantine D.; Chondros, Michalis K.
Abstract : A simple, small array of a few elevation probes is proposed for the estimation of wave directional spreading and the mean wave direction. This technique offers the possibility of such estimations through two comparable methods, that is, the Maximum Likelihood Method and the Maximum Entropy Method. It is noted that the latter method was combined with an approximate technique, based on a simple alternative calculation of sea surface's orthogonal slopes. The small array was proved to work well in both methods' applications to laboratory and modeled data. In summary, this paper proposes a simple array of probes and an approximate technique for the estimation of wave directional spreading, which can be used in association with laboratory, numerical, and field measurements, and can give sufficiently accurate results.